Tratamento de efluentes têxteis em reatores foto-oxidativos - Lenhard, Daiane Cristina (2010)
The objective of this work was to evaluate the possibility of treating effluents from textile industrial laundries by the process of photocatalytic oxidation. For this, a survey of data from the processes of industrial laundries from Maringá and from their effluent was conducted. Then, the treatment of effluents was evaluated in four different photocatalytic oxidation reactors: two on a bench scale (a thin film reactor, with immobilized catalyst, and a slurry reactor, with the catalyst in suspension) and two in a semi-pilot scale (a slurry reactor and a reactor with submerged lamps). Using the thin film reactor, in bench scale, tests were conducted using mercury vapor lamps of high- and low-pressure. The results obtained using the high pressure lamps were better than the ones obtained using the low pressure lamps. In the tests using the slurry reactor, different parameters were evaluated for the treatment of effluents from three laundries aiming to obtain the best experimental conditions for each one. For this, an experimental design with five factors at two levels was accomplished. The best conditions obtained for the effluent from one of the laundry were used for subsequent experiments in bench scale and also in a semi-pilot. The best decolorization results were obtained using the slurry reactor, which is probably due to the higher contact area obtained in this configuration. In the slurry reactor, on semi-pilot scale, the use of analytical grade titanium dioxide and commercial titanium dioxide as well as the combination of analytical grade catalyst and hydrogen peroxide was evaluated. The best results were obtained using the analytical grade titanium dioxide and commercial titanium dioxide combined with hydrogen peroxide. In three conditions, it was possible to reuse the catalyst four times. The use of commercial titanium dioxide in different concentrations was also evaluated and the best results were obtained using 1 g.L-1 of catalyst. Tests were carried out to verify the toxicity of textile effluents before and after treatment by photo-oxidative process using the slurry reactor. For these tests the micro-crustacean Artemia salina was used. The tests indicated a reduction in toxicity of the effluent after the treatment, therefore, it can be inferred that the intermediate compounds formed after the reaction are not toxic. The analyses of the solid waste generated in the treatments using the slurry reactor, on semi-pilot scale, were also accomplished. They were classified as CLASS II-B, or non-hazardous and non-inert, and should be disposed of in industrial landfill specific for this class of solid waste. Using the reactor with submerged lamps, on semi-pilot scale, the catalyst was not used. Only hydrogen peroxide was used, as an auxiliary oxidant. The results, however, were not promising and there were no significant decolorization of the effluent.